2015
DOI: 10.2134/jeq2014.06.0279
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Thermolysis Conditions for Soil Carbon Storage on Plant Residue Burning: Modeling the Trade-Off between Thermal Decomposition and Subsequent Biodegradation

Abstract: Field burning of plant biomass is a widespread practice that provides charred materials to soils. Its impact on soil C sequestration remains unclear due to the heterogeneity of burning products and difficulty in monitoring the material's biodegradation in fields. Basic information is needed on the relationship between burning conditions and the resulting quantity/quality of residue-derived C altered by thermal decomposition and biodegradation. In this study, we thermolyzed residues (rice straw and husk) at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Among the low-density fractions (F1-F2), ∆ 14 C was negatively correlated with the aromaticity index based on solid-state 13 C NMR spectroscopy (ratio of aromatic-C to O-alkyl-C, r 2 = 0.79, p < 0.001, using data from [53]) as well as with C:N ratio (Figure 2b). Burning and charring of plant residues increase their aromaticity, and remaining materials have higher stability against microbial degradation [62][63][64]. Thus, these negative correlations in F1-F2 suggest the presence of old pyrogenic, thus recalcitrant C. This interpretation is further supported by the high abundance of shiny dark-colored fragments in mixture with decaying plant litter based on light microscopic observation in F2 of Till-1 soil [42].…”
Section: Insights From Radiocarbon Analysis: Two Pools Of Stable Cmentioning
confidence: 83%
“…Among the low-density fractions (F1-F2), ∆ 14 C was negatively correlated with the aromaticity index based on solid-state 13 C NMR spectroscopy (ratio of aromatic-C to O-alkyl-C, r 2 = 0.79, p < 0.001, using data from [53]) as well as with C:N ratio (Figure 2b). Burning and charring of plant residues increase their aromaticity, and remaining materials have higher stability against microbial degradation [62][63][64]. Thus, these negative correlations in F1-F2 suggest the presence of old pyrogenic, thus recalcitrant C. This interpretation is further supported by the high abundance of shiny dark-colored fragments in mixture with decaying plant litter based on light microscopic observation in F2 of Till-1 soil [42].…”
Section: Insights From Radiocarbon Analysis: Two Pools Of Stable Cmentioning
confidence: 83%
“…for husk and ~0.6% for straw (Kajiura et al, 2015). Ashed husk residues were obtained from a mill in Battambang, Cambodia where fresh husk is used as a fuel source and incompletely combusted at ~450° C, as is done in some rice-growing countries (Haefele et al, 2009;Savant et al, 1997b).…”
Section: Soil Sampling and Experimental Set-upmentioning
confidence: 99%
“…produced under the higher temperature and low-oxygen concentration shows higher tolerance for decomposition (Kajiura et al 2015), CO 2 and CH 4 emission induced by biochar might be mitigated using decomposition-resistant biochar. Generally, biochar has porous micro-space (Nguyen et al 2004;Yu et al 2006) and biochar application can improve soil water holding properties (Rondon et al 2006).…”
Section: Methane Emission and C Release From A Rice Paddy Fieldmentioning
confidence: 99%
“…Because applied biochar in this study was produced at relatively high temperature, it was assumed that the biochar contained little decomposable C. Kajiura et al (2015) simulated that biochar made by rice straw and husk under high temperature (> 500°C) was hardly decomposed for 1000 years. Our study, however, indicated that biochar produced under high temperatures potentially contains decomposable C in field conditions, though the material of the biochar in their study was different than in Kajiura et al (2015). Moreover, the higher decomposition rate of biochar C in this study might also result in the acceleration of the microbial activity by biochar application.…”
Section: Methane Emission and C Release From A Rice Paddy Fieldmentioning
confidence: 99%
See 1 more Smart Citation